2015
DOI: 10.1097/aln.0000000000000765
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intraoperative Hypotension with Acute Kidney Injury after Elective Noncardiac Surgery

Abstract: In this analysis, postoperative AKI is associated with sustained intraoperative periods of MAP less than 55 and less than 60 mmHg. This study provides an impetus for clinical trials to determine whether interventions that promptly treat IOH and are tailored to individual patient physiology could help reduce the risk of AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
426
4
14

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 584 publications
(465 citation statements)
references
References 29 publications
21
426
4
14
Order By: Relevance
“…Our findings were consistent with those reported in previous studies by Walsh et al [9] (average age, approximately 55 years) and Sun et al [10] (average age, approximately 62.9 years). In a retrospective cohort of 18,989 patients who underwent noncardiac procedures, Walsh et al found a graded relationship between more than 5 min spent with a MAP of less than 55 mm Hg or a MAP of 55 mm Hg to 59 mm Hg and stage I AKI.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings were consistent with those reported in previous studies by Walsh et al [9] (average age, approximately 55 years) and Sun et al [10] (average age, approximately 62.9 years). In a retrospective cohort of 18,989 patients who underwent noncardiac procedures, Walsh et al found a graded relationship between more than 5 min spent with a MAP of less than 55 mm Hg or a MAP of 55 mm Hg to 59 mm Hg and stage I AKI.…”
Section: Discussionsupporting
confidence: 83%
“…Sun et al [10] performed another large retrospective analysis regarding the duration of IOH and its effect on AKI. When the intraoperative MAP was less than 60 mm Hg for more than 20 min or less than 55 mm Hg for more than 10 min there was an increased risk of postoperative AKI (defined as a more than 50% or 0.3 mg dL –1 increase in serum creatinine concentration).…”
Section: Introductionmentioning
confidence: 99%
“…Is the method appropriate to investigate the optimal threshold of blood pressure? On the other hand, in patients who underwent non-cardiac surgery, the time spent below intraoperative MAP of 55–60 mm Hg has been strongly associated with increased risk of postoperative AKI [8, 9]. The primary outcome in these studies was not progression to severe-stage AKI, and not all patients were admitted to the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the association between blood pressure and the progression to stage-3 oliguric AKI, we considered the cumulative hypotension duration as the most clinically relevant variable of blood pressure parameters based on recent studies [8, 9]. Here, we set three hypotension thresholds: MAP of 65, 70, and 75 mm Hg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation